The Impact of Covid-19 Pandemic on the MSMEs Economy in Rawa Pening Eco-tourism (Case Study on Eco-tourism in Asinan Village, Bawen Sub-district, Semarang Regency) - Pambudi, Rakhmat Dwi; Islami, Laily Tasya; Imron, Ali; Syakur, Riza Rizki Faozan (Forum Ilmu Sosial, 2021)
Rawa Pening has been famously known as a potential tourism site seen from its multiple natural and artificial attractions. During the Covid-19 pandemic, the numbers of visitors coming to the Asinan Village Ecotourism can even be said to be stable. This study aims to reveal the visitors' characteristics, the impact of Covid-19 on the MSMEs actors' economy, and the strategy of the Asinan Village Ecotourism in Rawa Pening. This study was qualitative descriptive. Respondents taken were visitors and MSMEs actors in the Asinan Village Ecotourism. The results indicate that the Covid-19 impacts the MSMEs actors' economy at the Asinan Village Ecotourism. Even though tourism still stands and comes up better than other sites—especially on weekends, most MSMEs actors find their income decreased. This condition is due to the escalating number of MSMEs actors, while the buying interest on the visitors tends to go lower. The decline can be influenced by changing purchasing power, consumption behavior dynamics, and social distancing as a part of the health protocols implementation.